Tracing evolutionary and developmental implications of mitochondrial stoichiometric shifting in the common bean - Arrieta Montiel, MP; Lyznik, A; Woloszynska, M; Janska, H; Tohme, Joseph M.; Mackenzie, S (2001)
The recombination and copy number shifting activities of the plant mitochondrial genome are widely documented across plant genera, but these genome processes have not been as well examined with regard to their roles in plant evolution. Because of the extensive plant collections of Phaseolus spp and the degree to which cytoplasmic male sterility (cms) has been characterized in the common bean, this system would be valuable for investigating mitochondrial genome dynamics in natural populations. We have used the cms-associated sequence pvs-orf239 as a mitochondrial genetic marker for these studies and have demonstrated its universal presence throughout a diversity of undomesticated Phaseolus lines. Within these populations, the pvs-orf239 sequence is present in high copy number in approximately 10% of the lines, but substoichiometric in all others. This mitochondrial sequence, derived apparently by at least two recombination events, is well conserved with two point mutations identified that are both apparently silent with regard to the sterility phenotype. A putative progenitor sequence was identified in Phaseolus glabelus in substoichiometric levels, suggesting that the present-day pvs-orf239 sequence was likely introduced substoichiometrically. Copy number shifting within the mitochondrial genome results in a 1000- to 2000-fold change, so that substoichiometric forms are estimated at less than one copy per every 100 cells. On the basis of PCR analysis of root tips, we postulate that a mitochondrial "transmitted form" resides within the meristem to assure transmission of a complete genetic complement to progeny.